Persepsi Guru Teknik Gambar Bangunan Tentang Kurikulum 2013 - Novi Ameliyana; Dadang Suyadi (LPPM Universitas Negeri Jakarta, 2013)
This study aimed to determine the perceptions of teachers about curriculum drawing technique building 2013. Where the research was conducted in Central Jakarta SMK 1 , SMK Negeri 56 Jakarta Utara , SMK Negeri 52 Jakarta Timur , SMK Negeri 26 Jakarta Timur , and SMK Negeri 35 Jakarta west . This study took place in November 2013 held at SMK in Jakarta on teacher drawing technique building .In this study using a survey method using a Guttman scale of 1-0 . The population in this study were teachers of engineering drawings in class X which implement the curriculum in 2013 the number of 19 respondents . The number of samples in this study were 19 teachers who teach engineering drawings in class X. In this study sample technique used is total sampling . To test the validity of the poll / questionnaire using the formula for the coefficient point biserial and reliability test using the KR - 21 formula . Based on the results of data processing questionnaires that are valid and reliable at the level of reliability that can be included in the criteria is as high as with R11 = 0.845 with the statement as much as 40 points .The results of processing the data in the study showed that teachers' perceptions of curriculum building drawing technique in 2013 in preparation indicator curriculum in 2013 has a positive perception with a percentage of 68.19 %, this can be said image building techniques teachers can welcome the curriculum in 2013 . Regarding the indicators of the basic concepts of curriculum 2013 image building techniques teachers have a positive perception with the percentage of 75.44 % means that teachers have to know the technique of building a picture of the concept of curriculum in 2013 and for indicators of teacher lesson plans engineering drawing of the building gives a positive perception of the learning plan curriculum 2013 with a percentage of 56.89 % means that teachers have to know how about planning curriculum learning in 2013 .